AgI‐Promoted Difluoromethylation of Isocyanides To Give Difluoromethylated Phenanthridines. Issue 22 (9th June 2017) - Wan, Wen; Xu, Xiaochen; Chen, Yunrong; Jiang, Haizhen; Wang, Yong; Deng, Hongmei; Hao, Jian
Abstract : An Ag I ‐mediated ethoxycarbonyldifluoromethylation of isocyanides has been developed. This radical cascade reaction involves the addition of difluoromethylene radical to the isocyanide functionality, and subsequent homolytic aromatic substitution to give difluoromethylated phenanthridines with a good functional‐group tolerance. Abstract : A convenient synthesis of ethoxycarbonyldifluoromethylated phenanthridines has been developed. The reaction involves an Ag I ‐mediated cascade gem ‐difluoromethylenation/cyclization of isocyanides with Me3 SiCF2 CO2 Et under mild reaction conditions.